2011
DOI: 10.1158/1535-7163.mct-11-0294
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Insulin-like Growth Factor-1 Receptor Induces Resistance to Epidermal Growth Factor Receptor Antagonism in Head and Neck Squamous Carcinoma Cells

Abstract: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) have poor efficacy in head and neck squamous cell carcinoma (HNSCC). Because the insulin-like growth factor-1 receptor (IGF1R) generates potent prosurvival signals and has been implicated in therapeutic resistance, its ability to induce resistance to EGFR-TKIs was studied in vitro. Five HNSCC cell lines demonstrated reduced sensitivity to the EGFR-TKI gefitinib when the IGF1R was activated. In SCC-25 and Cal27 cells, gefitinib inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 36 publications
5
84
0
Order By: Relevance
“…Li et al demonstrated that the expression of JUN in fibroblasts in the tumour microenvironment can promote the secretion of IGF-1. They also showed IGF-1 acting as a paracrine molecule that stimulates epithelial cell proliferation [29,30]. IGF-1 receptor (IGF-1R) activation was also found to be able to suppress anoikis and hence to promote the development of metastases [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al demonstrated that the expression of JUN in fibroblasts in the tumour microenvironment can promote the secretion of IGF-1. They also showed IGF-1 acting as a paracrine molecule that stimulates epithelial cell proliferation [29,30]. IGF-1 receptor (IGF-1R) activation was also found to be able to suppress anoikis and hence to promote the development of metastases [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, cross-talk between the IGF1R and EGFR receptor has been shown to result in compensation and resistance during targeted inhibition of either receptor. 11 Finally, various preclinical studies have shown improved activity when both IGF1R and EGFR are inhibited concomitantly. 12,13 Given that anti-IGF1R and anti-EGFR antibodies have shown toxicity clinically, it is important to study the combined effects of anti-IGF1R and anti-EGFR treatment quantitatively.…”
Section: Resultsmentioning
confidence: 99%
“…For a long time, a number of studies have noticed a crosstalk between the IGF-1 and EGFR signaling pathways [21], [22], [23]. Their synergistic interactions are thought to be associated with the acquired resistance to EGFR-tyrosine kinase inhibitors like gefitinib [22].…”
Section: Chiefly Produced By Receptor Functionmentioning
confidence: 99%